9514 1404 393
Answer:
f(x) = (2x -9)/(x -2)
Step-by-step explanation:
We can use the fact that g(g^-1(x)) = x.
[tex](f\circ g)(x) = f(g(x))\\\\(f\circ g)(g^{-1}(x))=f(g(g^{-1}(x)))=f(x)[/tex]
So, we need to know the inverse of g(x):
x = g(y)
x = 5y +2
x -2 = 5y
y = (x -2)/5 . . . . inverse of g(x)
Then we have ...
[tex]f(x)=(f\circ g)(g^{-1}(x))=(f\circ g)\left(\dfrac{x-2}{5}\right)\\\\f(x)=\dfrac{2\left(\dfrac{x-2}{5}\right)-1}{\left(\dfrac{x-2}{5}\right)}=\dfrac{2x-4-5}{x-2}\\\\\boxed{f(x)=\dfrac{2x-9}{x-2}}[/tex]